Solving generalized eigenvalue problems for large scale fluid-structure computational models with mid-power computers. (1st August 2018) - Akkaoui, Q.; Capiez-Lernout, E.; Soize, C.; Ohayon, R.
Highlights: Novel algorithms for large scale fluid-structure models with mid-power computers. Fluid-structure computational model with sloshing and capillarity. Solving generalized eigenvalue problems for constructing reduced-order bases. Evaluation of the algorithms efficiency as a function of the number of Dofs. Abstract: This article proposes a method for solving generalized eigenvalue problems on medium-power computers with a moderate memory in the particular context of studying fluid-structure systems with sloshing and capillarity. This research was performed following many RAM problems encountered when computing the modal characterization of the system studied. The methodology proposed is one solution to reduce RAM and time required for the computation, by using methods such as double projection or subspace iterations.